New Ecuadorian and Colombian Lamiinae (Coleoptera, Cerambycidae) - Vlasak, Josef; Nascimento, Francisco Eriberto Lima; Santos-Silva, Antonio (Zootaxa, 2025)
Three new species are described: Nealcidion chloroxanthon sp. nov. from Ecuador and N. antonellum sp. nov. from Colombia (Acanthocinini); and Antodice apicalis sp. nov. from Ecuador (Aerenicini).